Deliberations about deliberative methods: issues in the design and evaluation of public participation processes - Abelson, Julia; Forest, Pierre-Gerlier; Eyles, John; Smith, Patricia; Martin, Elisabeth; Gauvin, Francois-Pierre (Social Science & Medicine, 2003)
A common thread weaving through the current public participation debate is the need for new approaches that emphasize two-way interaction between decision makers and the public as well as deliberation among participants. Increasingly complex decision making processes require a more informed citizenry that has weighed the evidence on the issue, discussed and debated potential decision options and arrived at a mutually agreed upon decision or at least one by which all parties can abide. We explore the recent fascination with deliberative methods for public involvement first by examining their origins within democratic theory, and then by focusing on the experiences with deliberative methods within the health sector. In doing so, we answer the following questions “What are deliberative methods and why have they become so popular? What are their potential contributions to the health sector?” We use this critical review of the literature as the basis for developing general principles that can be used to guide the design and evaluation of public involvement processes for the health-care sector in particular.
Keywords: Participation publique; Santé